CAUSES OF LETHAL OUTCOMES OF PATIENTS WITH AND WITHOUT TYPE 2 DIABETES MELLITUS IN A MULTIDISCIPLINARY HOSPITAL IN IRKUTSK DURING THE PEAK OF THE COVID-19 PANDEMIC - Olga Alexandrovna Ivanova; Dmitriy Andreevich Antipin; Sergey Germanovich Kuklin (Байкальский медицинский журнал)
Introduction. Numerous literature data report a significant increase in mortality during the peak of the incidence of COVID-19, even in patients without confirmed coronavirus infection. The most vulnerable group during this period were patients with diabetes mellitus (DM) due to more frequent comorbid conditions.Materials and methods. An analysis of all protocols for the autopsy of deceased patients for 2020 and 2021 was carried out. in a multidisciplinary hospital, when the institution provided emergency medical care to the population of the city of Irkutsk in the surgical and therapeutic profile without a confirmed coronavirus infection. Groups of patients with and without type 2 DM were analyzed separately by pairwise comparisons (92 groups of patients matched by sex and age).Results. An analysis of the annual dynamics of nosocomial mortality showed an increase in the indicator during the peak of the pandemic by about 2.5 times (in 2018 - 65 cases, in 2019 - 109 cases, in 2020 - 254 cases, in 2021 - 244 cases, in 2022 – 81 cases). In the structure of the causes of deaths in both groups, diseases associated with atherosclerosis dominated - in 44% of cases, significantly more often in the group of patients with DM (53% vs 36%, p≤0.05). Also, patients with DM had a higher incidence of stenosing coronary atherosclerosis (86% vs 73%, p=0.03). In second place in terms of frequency of occurrence were infectious causes of death - 16%, malignant neoplasms - 17%, comparable in both groups, as well as surgical pathology of the gastrointestinal tract (GIT) - 17%, which was more common in the group of patients without DM (24 % vs 10%, p≤0.05). An analysis of the immediate causes of death in patients without DM and with type 2 DM was comparable in most indicators, with the exception of the number of bleeding and posthemorrhagic anemia, which occurred in a larger percentage of cases in patients without DM (11% vs 3%, p = 0.003), which due to the predominance of surgical pathology of the gastrointestinal tract in these patients. Thus, the leading direct cause of death among all patients was pulmonary edema - in 81%, then in descending order - pulmonary embolism in 34%, sepsis in 23%, bleeding in 14%, acute myocardial infarction and peritonitis in 12% of cases. The analysis of comorbidities in both groups of patients did not reveal significant differences, with the exception of arterial hypertension, which was more common in patients with DM (76% vs 61%, p=0.03). Histological changes in the kidneys (glomerulosclerosis, interstitium sclerosis, arteriological alinosa) were equally common in patients without and with type 2 diabetes (92% vs 86%, p≥0.05), which is probably due to high comorbidity in both groups . Thus, signs of histologically confirmed pyelonephritis were detected in almost every second patient in the study groups (with DM - in 63%, without DM - in 65%, p≥0.05), which exceeds the literature data by 2-3 times.Conclusion. In a multidisciplinary hospital during the COVID-19 pandemic, there was a significant increase in mortality (by 2.5 times). In the structure of the causes of deaths in both groups, diseases associated with atherosclerosis dominated, significantly more often in the group of patients with DM. In the group of patients with DM, stenosing coronary atherosclerosis and arterial hypertension were more common. In patients without DM, one of the leading causes of mortality was surgical pathology of the gastrointestinal tract, which was accompanied by significantly higher cases of bleeding. Attention is drawn to the high frequency of histologically confirmed pyelonephritis in both groups (over 60%), which can make a significant contribution to thanatogenesis.